2022
DOI: 10.1007/s12144-022-03283-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual violence among male sexual minority college students in Guangdong, China: a cross-sectional study

Abstract: This study aims to provide an estimate of lifetime sexual violence (SV) among male sexual minority college students with differing sexual orientations and contribute to the evidence base on the association between SV experience, stress, and depressive symptoms. The data stemmed from the 2019 Internet Survey on HIV/AIDS and Sexual Health in Colleges and Universities in Guangdong province, China. Lifetime SV victimisation (including non-sexual harassment, physical contact sexual harassment, and rape), level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In another study conducted in Pakistan revels that, total of 225 instances of sexual abuse, including all types, were reported by respondents, of which 24 occurred too frequently, 35 occurred 10-50 times, and 166 occurred less than ten times [11]. In study conducted in China found that, 24.3% (350/1441) of the students reported having encountered sexual violence; of these, 23.4% (337/1441) had dealt with non-contact Juniper Online Journal of Public Health harassment, 8.8% (127/1441) had dealt with physical contact harassment, and 2.4% (35/1441) had been sexually assaulted at some point in their lives [12]. The probable reason for not getting any data of sexual abuse among the participants is their religious and cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…In another study conducted in Pakistan revels that, total of 225 instances of sexual abuse, including all types, were reported by respondents, of which 24 occurred too frequently, 35 occurred 10-50 times, and 166 occurred less than ten times [11]. In study conducted in China found that, 24.3% (350/1441) of the students reported having encountered sexual violence; of these, 23.4% (337/1441) had dealt with non-contact Juniper Online Journal of Public Health harassment, 8.8% (127/1441) had dealt with physical contact harassment, and 2.4% (35/1441) had been sexually assaulted at some point in their lives [12]. The probable reason for not getting any data of sexual abuse among the participants is their religious and cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, more international studies on sexual violence focused on the GBM population, regardless of the bond between victim and perpetrator. Some of their results report a 35.2% prevalence of non-consensual sex among men who have sex with men [ 21 ], 54.0% prevalence of sexual assault [ 22 ], 15.5% of physical SV, sexual assault, and stalking in the past 6 months [ 23 ], frequencies for sexual assault of 10.1% for cis gay men and 9.5% for cis bisexual men in the past year [ 24 ], 39% lifetime contact sexual violence and 29.2% lifetime non-contact sexual violence for bisexual men and 17.7% and 33.3% for gay men [ 25 ], prevalence of SV reaching 31.64% in gay men and 29.44% in bisexual men [ 26 ]. Although all the studies mentioned above conclude that SV in the GBM population is drastically higher than in heterosexual cissexual men and similar to heterosexual cissexual women, and also that trans people have a higher risk of victimization, the figures differ greatly among them due to a lack of clear delimitation in the concept of sexual violence (e.g., sexual coercion, sexual aggression, unwanted relationships, intimate partner violence, etc.).…”
Section: Introductionmentioning
confidence: 99%